Randomized Controlled Trial Between 24 And 48 Hours Nasal Packing after Sub Mucosal Resection - Sheraz Bashir,Arfat Jawaid, Faiz-ul-Hassan Nawaz (Journal of Rawalpindi Medical College, 2013)
Background: To compare 24-hours versus 48-hours nasal packing in terms of discomfort and effectiveness in preventing septal haematoma and bleeding after sub-mucosal resection of nasal septum. Methods: In this randomized controlled trial 160 patients of symptomatic deviated nasal septum (DNS) were included. The sample was randomly divided into two groups, A and B, consisting of 80 patients each. After sub-mucosal resection (SMR) under general anesthesia, bilateral nasal packing was done with paraffin gauze rolls. In Group A, nasal packs were removed after 24 hours. In Group B nasal packs were removed after 48 hours. After the removal of nasal packs bleeding ,septal haematomas and subjective discomfort were assessed. Results: One day (24 hours) nasal packing caused significantly less discomfort, as 28.75% patients had no discomfort as compared to only 5.0% patients in 48 hours nasal packing. However, difference in septal haematoma (2.5% in 24 hours group and 1.25% in 48 hours group) and bleeding (58.75% in 24 hours group and 62.5% in 48 hours group) was statistically insignificant. Conclusion: Twenty four hours nasal packing has significantly less discomfort as compared to 48 hours nasal packing. There is insignificant difference in bleeding and septal haematoma between 24 hours and 48 hours nasal packing.